The modulation of mRNA levels of MAOA by electroacupuncture and psychotherapy in patients with pathological internet use - Dai, Yu; Zhang, Chenchen; Zhang, Lingrui; Wen, Chao; Zhu, Tianmin (Frontiers in Psychiatry, 2022)
Objective The aim of this study was to observe the efficacy of electroacupuncture (EA) and psychotherapy (PT) effect on the mental status, sleep quality and impulsive trait in patients with pathological internet use, and to observe the changes of Monoamine oxidase type A (MAOA) messenger Ribonucleic acid (mRNA) levels in each group. Methods A total of 60 PIU patients were included for the present study. These patients were randomly divided into two groups: EA group and PT group. Baihui, Sishencong, Hegu, Neiguan, Shenmen, Taichong, Sanyinjiao and Xuanzhong were selected for acupuncture in the EA group, while group psychotherapy combined with individual psychotherapy was used for intervention in patients in the PT group. Young’s Internet addiction Test (IAT), Yale-Brown Obsessive-Compulsive Scale (Y-BOCS), Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Barratt Impulse Scale (BIS-11) and Pittsburgh Sleep Quality Index (PSQI) were used to observe the severity of Internet addiction, mental status, sleep quality and impulsive trait of all patients at baseline and 40th days of treatment; and MAOA mRNA data were collected at baseline and 40th days of treatment. Results Electroacupuncture and psychological intervention effectively reduced IAT, SAS, SDS, Y-BOCS, BIS and PSQI scores of PIU patients. After 40 days treatment, the MAOA expression of the PT group was increased, and there was no significant change in EA group. The correlation analysis indicated that IAT scores were positively correlated with SAS, SDS, Y-BOCS, BIS and PSQI at baseline. In addition, after treatment the EA group showed that the change in IAT scores was positively correlated with the change in Y-BOCS and BIS scores, and the PT group showed that the change in IAT scores was positively correlated with the change in SDS, BIS and PSQI scores. Conclusion The present study showed that electroacupuncture and psychological intervention can improve severity of Internet addiction, mental status, sleep quality and impulsive trait of PIU patients. Simultaneously, neurobiological changes may be the underlying mechanisms of psychotherapy for internet additcion.